Magnetic resonance imaging for accelerated assessment of drug effect and prediction of subsequent radiographic progression in rheumatoid arthritis: a study of patients receiving combined anakinra and methotrexate treatment. Issue 10 (18th March 2005) - Østergaard, M; Duer, A; Nielsen, H; Johansen, J S; Narvestad, E; Ejbjerg, B J; Baslund, B; Møller, J M; Thomsen, H S; Petersen, J
Abstract : Objectives: By MRI to assess the efficacy of addition of anakinra for controlling synovitis and stopping erosive progression in patients with clinically active RA despite receiving methotrexate, and to determine the predictive value of MRI for subsequent radiographic erosive progression. Methods: 100 mg anakinra subcutaneously/day was added to the treatment of 17 patients with clinically active RA despite methotrexate. MRI of the non-dominant wrist and 2nd-5th MCP joints (OMERACT evaluation) was performed at weeks 0, 12, and 36, and radiography of both hands and wrists (modified Sharp evaluation) at weeks 0 and 36. Results: MRI synovitis scores were not significantly changed. Radiography of both hands and wrists after 36 weeks showed erosive progression in 11 patients, and MRI after 12 weeks in 10 patients. Nine of 10 patients with MRI progression at 12 weeks had radiographic progression at 36 weeks. Baseline MRI synovitis and erosion scores, but no clinical/biochemical parameters, correlated significantly with subsequent erosive progression. Conclusion: Addition of anakinra did not significantly reduce MRI signs of synovitis, and most patients had progressive joint destruction. Baseline MRI findings predicted subsequent radiographic erosive progression. Unilateral wrist and MCP joint MRI after 12 weeks had a similar sensitivity for detection of erosive progression as bilateral hand and wrist radiography after 36 weeks.